Бекир Чобан-заденинъ миллий матбуатымызнынъ тарихине даир бакъышлары - Меметова, Л.А. (Культура народов Причерноморья, 2014)
В статье рассматриваются публикации великого тюрколога Бекира Чобан-заде, посвященные возникновению и дальнейшему становлению крымскотатарской периодической печати. Исследуются взгляды ученого по отношению к первым национальным изданиям, характеризуется их значимость в социальной жизни мусульман Крыма на рубеже XIX-XX столетий. Определяется роль критических заметок профессора Б. Чобан-заде о национальной периодике, послуживших необходимым материалом в осуществлении дальнейших научных изысканиях по истории национальной периодической печати. У статті розглядаються публікації великого тюрколога Бекіра Чобан-заде, присвячені виникненню і подальшому становленню кримськотатарської періодичної преси. Досліджуються погляди вченого стосовно першим національним виданням, характеризується їх значимість у соціальному житті мусульман Криму на рубежі XIX-XX століть. Визначається роль критичних заміток професора Б. Чобан-заде про національну видання, що послужили необхідним матеріалом у здійсненні подальших наукових розвідках з історії національної періодичної преси. The article deals with the publication of the great turkologist Bekir Choban-zade, dedicated to the emergence and further establishment of the Crimean Tatar periodicals. Characterizing historiographical data on the subject in question, indicating the variety of sources of linguistic, literary and biographical highlights, defining the little scrutiny of this problem and its relevance. Investigating functional features such periodicals as "Terdzhiman", "Vetan hadimi", explores the ideological orientation of publications and public position of their editorial staff. Studying scientist looks towards the first national publications, characterized by their importance in the social life of Muslims of Crimea on the XIX-XX centuries, and generally throughout the Russian Empire. The role of critical notes of Professor B. Choban-zade on national periodicals is defined as the necessary material in carrying out further scientific studies on the history of the national periodicals. Along with that considers the views of the other researchers and national publications, focuses on the importance of critical publications of scientist in this field.